Flood Hydrograph Generation for Kenyir Dam Using Hydrological Modeling System - Mohd Sidek L.; Razali J.; Marufuzzaman M.; Yalit M.R.; Radzi M.R.M.; Shabbir Hossain M. (Springer, 2023)
Among various dams owned by Tenaga Nasional Berhad (TNB) Malaysia, some were constructed in the early 1930s. Hence, these dams might be affected by severe storms after completion. Climate change affects the availability and distribution of water resources in space and time and the frequency of extreme rainfall events (PMP). Moreover, the probable maximum flood (PMF) designed before has increased and currently, some dams would be overtopped and caused floods in the downstream area. Thus, it is important to revise the PMP and the PMF values by using the notable storms of climate change as well as to generate flood hydrographs for water dams. In this research, Kenyir Lake is considered for sampling sites. The long record of rainfall and other meteorological data for all stations have been identified, collected, assembled, processed and used in the analyses to determine the PMP values and generation of PMF using HEC-HMS. The results showed that the inflow value for Kenyir is 23,923.1m3/s, whereas the outflow is 5,563.2m3/s. Finally, 5, 10, 50 and 100-year flood hydrographs for Kenyir dam are proved that it is expected to be safe from overtopping under the PMF condition founded by this research. 2020, Springer Nature Singapore Pte Ltd.